Triggers of acute attacks of gout, does age of gout onset matter?: a primary care based cross-sectional study - Kunze, Gotthard; Abhishek, Abhishek; Valdes, Ana M.; Jenkins, Wendy; Zhang, Weiya; Doherty, Michael (Public Library of Science, 2017)
Objectives